Adhesive film and single or multilayer film
Patent Information
- Application Number
- CN202580021435.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2025-03-26
- Publication Date
- 2026-10-20
AI Technical Summary
[0034]按照本发明的一实施方式,能够提供一种变形加工时的耐白化性优异的粘接性膜。按照本发明的一实施方式,能够提供一种变形加工时的耐白化性优异的单层或多层膜。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to adhesive films and single-layer or multi-layer films. Background Technology
[0002] Polypropylene has long been widely used as a thermoplastic molding material with excellent rigidity, heat resistance, and transparency. Because polypropylene is a non-polar material, it has poor adhesion to polar materials such as ethylene-vinyl alcohol copolymers. To improve adhesion, a well-known technique is to modify polypropylene with unsaturated carboxylic acids or their derivatives. Furthermore, due to its poor flexibility, soft rubber components are usually incorporated into polypropylene when it is used as an adhesive.
[0003] For example, in Patent Document 1, a resin composition containing an propylene polymer (A), a soft propylene copolymer (B), a polyolefin (C) containing structural units derived from unsaturated carboxylic acids and / or their derivatives, and an ethylene polymer (D) is disclosed as a resin composition capable of forming a film with excellent adhesion, especially excellent adhesion at low heat, and excellent resistance to whitening during deformation processing.
[0004] For example, in Patent Document 2, an adhesive resin composition containing a propylene polymer (A), a modified polyolefin (B), and an ethylene polymer (C) is disclosed as an adhesive resin composition capable of forming a battery packaging film with excellent electrolyte resistance and an electrode sealing material for lithium-ion batteries.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: International Publication No. 2019 / 176403
[0008] Patent Document 2: International Publication No. 2023 / 022168 Summary of the Invention
[0009] The problem that the invention aims to solve
[0010] The film formed by the resin composition described in Patent Document 1 still needs further improvement in terms of resistance to whitening during deformation processing.
[0011] One embodiment of the present invention aims to provide an adhesive film with excellent resistance to whitening during deformation processing. Another embodiment of the present invention aims to provide a single-layer or multi-layer film with excellent resistance to whitening during deformation processing.
[0012] Technical solutions for solving the problem
[0013] The technical solutions to the above problems include the following implementation methods.
[0014] <1> An adhesive film, comprising:
[0015] 50 to 89.9 parts by weight of propylene polymer (A) that meets the following (A1);
[0016] 0.1–20 parts by mass of modified polyolefin (B) containing structural units derived from at least one of unsaturated carboxylic acids and their derivatives; and
[0017] 10 to 30 parts by mass of ethylene polymer (C) that meets the following (C1) to (C3) (wherein, the total of (A), (B) and (C) is set as 100 parts by mass).
[0018] The area proportion of island phases observed in cross-sections perpendicular to the membrane surface and including the MD direction is 17–28%.
[0019] (A1) Relative to the total mass of the aforementioned propylene polymer (A), the content of propylene polymer (a-2) in the aforementioned propylene polymer (A) with a melting point (Tm) less than 120°C as observed in differential scanning calorimetry is 20-100% by mass.
[0020] (C1) contains an ethylene-α-olefin copolymer (c-1).
[0021] (C2) The melt flow rate, measured according to ASTM D1238 at 230°C and a load of 2.16 kg, is 0.1–10 g / 10 min.
[0022] (C3) The content of the above copolymer (c-1) relative to the total mass of the above ethylene polymer (C) is 40 to 100 by mass.
[0023] <2> According to the adhesive film described in <1>, wherein,
[0024] The composition of the marine phase observed in a cross-section perpendicular to the film surface and including the MD direction, and the melt flow rate A measured according to ASTM D1238 at 230°C and a load of 2.16 kg, are compared with...
[0025] The composition of island phases observed in a cross-section perpendicular to the film surface and including the MD direction is the ratio of the melt flow rate B (MFR) measured according to ASTM D1238 at 230°C and a load of 2.16 kg. A / MFR B () is 2 or more but less than 5.
[0026] <3> A single-layer or multi-layer membrane, wherein the single-layer or multi-layer membrane has the adhesive membrane described in <1> or <2>.
[0027] <4> A multilayer film, wherein:
[0028] At least one layer of the adhesive film described in <1> or <2>; and
[0029] Selected from at least one layer comprising a metal layer, a polyolefin layer, and a polar resin layer.
[0030] The adhesive membrane is bonded to at least one layer selected from the metal layer, polyolefin layer and polar resin layer.
[0031] <5> The adhesive film according to <1> or <2>, wherein the adhesive film is a battery packaging film.
[0032] <6> The adhesive film according to <1> or <2>, wherein the adhesive film is an electrode sealing material for lithium-ion batteries.
[0033] Invention Effects
[0034] According to one embodiment of the present invention, an adhesive film with excellent resistance to whitening during deformation processing can be provided. According to another embodiment of the present invention, a single-layer or multi-layer film with excellent resistance to whitening during deformation processing can be provided. Detailed Implementation
[0035] The following describes the details of specific embodiments of the present invention.
[0036] Although the description of the constituent conditions described below is based on a representative embodiment of the present invention, the present invention is not limited to the following embodiments under any circumstances, and can be implemented with appropriate modifications within the scope of the present invention.
[0037] In this specification, the numerical range indicated by “~” means the range including the values recorded before and after “~” as the lower and upper limits.
[0038] It should be noted that, in this specification, when referring to the amount of each component in the composition, if there are multiple substances in the composition that are equivalent to each component, unless otherwise specified, it means the total amount of the multiple substances present in the composition.
[0039] In this specification, unless otherwise specified, the units listed before and after the "~" indicating a range of values represent the same units.
[0040] In this specification, a combination of two or more preferred embodiments is a more preferred embodiment.
[0041] In this specification, MD stands for Machine Direction, which refers to the flow direction during adhesive film formation.
[0042] The present invention will now be described in more detail.
[0043] The adhesive membrane of the present invention comprises: 50 to 89.9 parts by mass of a propylene polymer (A) satisfying (A1) below; 0.1 to 20 parts by mass of a modified polyolefin (B) containing structural units derived from at least one of unsaturated carboxylic acids and their derivatives; and 10 to 30 parts by mass of an ethylene polymer (C) satisfying (C1) to (C3) below (wherein the total of (A), (B) and (C) is set to 100 parts by mass), wherein the area ratio of island phases observed in a cross section perpendicular to the membrane surface and including the MD direction is 17 to 28%.
[0044] The adhesive film of the present invention, having the above-described structure, exhibits excellent resistance to whitening during deformation processing. While the reason for this is not yet clear, the inventors infer that the mechanism is as follows:
[0045] When adhesive membranes are processed and deformed, stress is applied to the interface between the continuous phase (ocean phase) and the dispersed phase (island phase). Therefore, it is presumed that when the resin component, as the dispersed phase (island phase), is sparsely dispersed in the membrane, the stress on the interface becomes greater, making membrane whitening more likely during processing and deformation. Furthermore, it is presumed that if the resin component as the dispersed phase (island phase) is over-dispersed, although the domain size of the dispersed phase (island phase) will decrease, a large amount of dispersed phase (island phase) will exist in the continuous phase (ocean phase), making membrane whitening more likely during processing and deformation.
[0046] On the other hand, the adhesive film of the present invention contains specific amounts of specific propylene polymers (A), modified polyolefins (B), and specific ethylene polymers (C), thus readily forming a continuous phase (ocean phase) and a dispersed phase (island phase) in the adhesive film. Furthermore, the area ratio of the island phase observed in the cross-section of the adhesive film of the present invention is 17-28%, therefore, even when the adhesive film is processed and deformed, the morphology (microstructure) of the adhesive film can be controlled, thereby suppressing whitening of the film during deformation processing, i.e., exhibiting excellent whitening resistance during deformation processing.
[0047] <Island Structure>
[0048] The area ratio of island phases observed in the adhesive membrane in a cross section perpendicular to the membrane surface and including the MD direction is 17-28%, preferably 20-25%.
[0049] The adhesive film preferably forms an island structure (i.e., a finely dispersed structure), and more preferably, it forms an island structure in which the continuous phase (sea phase) is composed of a propylene-based polymer (A) and a modified polyolefin (B), and the dispersed phase (island phase) is composed of the aforementioned ethylene-based copolymer (C). Because the adhesive film forms an island structure, and the area ratio of the island phase is within the aforementioned range, the morphology (fine structure) of the adhesive film is controlled. Therefore, during the deformation of the adhesive film during processing, the stress acting on the interface between the continuous phase (sea phase) and the dispersed phase (island phase) is easily dispersed, making whitening difficult to occur. Thus, it exhibits excellent resistance to whitening during deformation processing.
[0050] The marine and island phases in the adhesive membrane can be confirmed by transmission electron microscopy (TEM). Furthermore, the area ratio of the island phases can be determined using the methods described in the examples below.
[0051] When determining the area ratio of island phases in the adhesive membrane of the multilayer membrane described later, the same method as used to determine the area ratio of island phases in the adhesive membrane described above is employed.
[0052] The area ratio of the island phase and the marine phase can be adjusted by changing the MFR ratio of the propylene polymer (A) and the modified polyolefin (B) to the ethylene copolymer (C) (i.e., the MFR of the marine phase / the MFR of the island phase), thereby altering the morphology in the adhesive film.
[0053] The area ratio of island and marine phases in the adhesive membrane can also be adjusted by changing the content ratio of propylene polymer (A) and modified polyolefin (B) to ethylene copolymer (C) in the composition constituting the membrane.
[0054] The ratio of the melt flow rate A of the marine phase composition observed in a cross section perpendicular to the membrane surface and including the MD direction, measured according to ASTM D1238 at 230°C and a load of 2.16 kg, to the melt flow rate B of the island phase composition observed in a cross section perpendicular to the membrane surface and including the MD direction, measured according to ASTM D1238 at 230°C and a load of 2.16 kg (MFR) A / MFR B The MFR is preferably 2 to 5, more preferably 3 to 4.5. A / MFR B Within the above range, it exhibits excellent resistance to whitening.
[0055] Melt flow rate A and melt flow rate B can be obtained by the methods described in the examples below.
[0056] The following is a detailed description of the components contained in the adhesive film.
[0057] <<Propylene Polymers (A)>>
[0058] The above-mentioned propylene polymer (A) satisfies (A1).
[0059] [Condition (A1)]
[0060] Relative to the total mass of the aforementioned propylene polymer (A), the content of the propylene polymer (a-2) in the aforementioned propylene polymer (A) with a melting point (Tm) less than 120°C as observed in differential scanning calorimetry is 20 to 100% by mass, preferably 20 to 50% by mass, more preferably 20 to 45% by mass, and even more preferably 20 to 40% by mass.
[0061] The propylene polymer (a-2) may contain only one type or two or more types in combination. When it contains two or more propylene polymers (a-2), the content of the propylene polymer (a-2) is the total content of propylene polymers (a-2) contained in the propylene polymer (A).
[0062] The melting point (Tm) of the propylene polymer (a-2) observed in differential scanning calorimetry is preferably below 100°C, more preferably 60–100°C. When the melting point (Tm) is within the above range, it is easier to obtain an adhesive film with excellent and uniform adhesion at both room temperature and high temperature. It should be noted that the above melting point (Tm) can be obtained according to the following measurement conditions.
[0063] (Measurement conditions)
[0064] Melting point (Tm) was determined using a differential scanning calorimeter (DSC) (e.g., a PerkinElmer DSC8500 device). Approximately 5 mg of sample was sealed in an aluminum dish. The temperature profile was set as follows: the temperature was increased from room temperature to 230°C at a rate of 10°C / min, held at 230°C for 10 minutes, then decreased to 30°C at a rate of 10°C / min, held at 30°C for 1 minute, and then increased to 230°C at a rate of 10°C / min. The peak temperature at the second heating (or the highest peak temperature if multiple peaks exist) was taken as the melting point (Tm).
[0065] <<Propylene Polymers (a-2)>>
[0066] There are no particular limitations on the propylene polymer (a-2) as long as it meets the above (A1), but it is preferred to be a propylene copolymer containing structural units derived from butene, and the content of structural units derived from ethylene is less than 1 mol% relative to the total number of moles of structural units constituting the polymer, and more preferably a propylene-butene copolymer.
[0067] It should be noted that the above-mentioned propylene polymer (a-2) is a different polymer from the modified polyolefin (B) described below.
[0068] The content of butene-derived structural units in the propylene polymer (a-2) is preferably 10 to 30 mol% relative to the total number of moles of structural units constituting the polymer, more preferably 12 to 28 mol%. The content of propylene-derived structural units in the propylene polymer (a-2) is preferably 70 to 90 mol% relative to the total number of moles of structural units constituting the polymer, more preferably 72 to 88 mol%.
[0069] The melt flow rate (MFR) of the propylene polymer (a-2), measured according to ASTM D1238 at 230°C and a load of 2.16 kg, is preferably 0.1 to 50 g / 10 min, more preferably 0.5 to 10 g / 10 min. When the MFR is within the above range, an adhesive layer with a better balance between flexibility and mechanical strength and higher adhesion can be obtained.
[0070] The preferred density of the propylene polymer (a-2) based on JIS K7112 is 860–900 kg / m³. 3 More preferably, it is 870–900 kg / m³. 3 .
[0071] The molecular weight distribution (Mw / Mn) of the propylene polymer (a-2) as determined by gel permeation chromatography (GPC) is preferably 1.5 to 5.0, more preferably 1.8 to 4.0.
[0072] The method for manufacturing the propylene polymer (a-2) is not particularly limited, and it can be manufactured by known methods using known catalysts such as Ziegler-Natta catalysts and metallocene catalysts. Furthermore, the propylene polymer (a-2) is preferably a polymer that satisfies moldability and has strength capable of withstanding the use of the resulting adhesive film. Without impairing the effects of the present invention, there are no particular limitations on the stereoregularity and molecular weight of the propylene polymer (a-2). Additionally, commercially available resins can also be used directly as the propylene polymer (a-2).
[0073] <<Propylene Polymers (a-1)>>
[0074] The propylene polymer (A) preferably includes the propylene polymer (a-1) with a melting point (Tm) of 120°C or higher as observed in differential scanning calorimetry. From the viewpoint of excellent whitening resistance, the melting point (Tm) of the propylene polymer (a-1) is preferably 120–170°C, more preferably 130–165°C.
[0075] The melting point (Tm) was determined using the same method as that used for the determination of the melting point (Tm) in the aforementioned propylene polymer (a-2).
[0076] As for the aforementioned propylene-based polymer (a-1), there are no particular limitations as long as the melting point (Tm) is 120°C or higher. Examples include propylene homopolymers and copolymers formed by propylene and α-olefins with 2 to 20 carbon atoms other than propylene. Among these, examples of α-olefins with 2 to 20 carbon atoms other than propylene include ethylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. Even among these olefins, ethylene and α-olefins with 4 to 10 carbon atoms are preferred as α-olefins with 2 to 20 carbon atoms other than propylene.
[0077] Copolymers formed by propylene and α-olefins with 2 to 20 carbon atoms other than propylene can be random copolymers or block copolymers.
[0078] The content of structural units derived from the α-olefin is preferably 35 mol% or less, more preferably 30 mol% or less, even more preferably 10 mol% or less, and particularly preferably 5 mol% or less, relative to the total molar number of structural units constituting the copolymer. Furthermore, the content of structural units derived from the α-olefin is preferably 1 mol% or more, more preferably 2 mol% or more, relative to the total molar number of structural units constituting the copolymer.
[0079] There are no particular restrictions on the form of the aforementioned propylene polymer (a-1); either isotactic or syndiotactic structures are acceptable.
[0080] That is, as forms of the aforementioned propylene polymers (a-1), isotactic propylene polymers and syndiotactic propylene polymers can be cited.
[0081] As isotactic propylene polymers (hereinafter also referred to as "isotactic propylene polymers"), homopolymers are an example of homopolymers with excellent heat resistance. Furthermore, as homopolymers, known homopolymers with a copolymer content other than propylene typically of 3 mol% or less can be cited as examples. Moreover, block polypropylenes are an example of a polypropylene that offers a good balance between heat resistance and flexibility. Block polypropylenes, for example, are known block polypropylenes that typically contain 3 to 30 wt% n-decane-soluble rubber components. Atactic polypropylenes, which offer a good balance between flexibility and transparency, are known atactic polypropylenes whose melting peak, as measured by differential scanning calorimetry (DSC), is typically 120°C or higher, preferably in the range of 130°C to 150°C.
[0082] Isopropyl propylene polymers can be appropriately selected from the above-mentioned sources based on the target physical properties. Furthermore, the aforementioned isotactic propylene polymers can utilize two or more of the aforementioned polypropylene components with different melting points and rigidities.
[0083] Such isotactic propylene polymers can be produced by polymerizing propylene or copolymerizing propylene with other α-olefins, for example, in the presence of a Ziegler-Natta catalyst consisting of a solid catalyst component containing magnesium, titanium, halogens and electron donors, an organoaluminum compound and an electron donor, or a metallocene catalyst in which a metallocene compound is used as one of the catalyst components.
[0084] As a syndiotactic propylene polymer, it is preferred to contain at least 90 mol% of structural units derived from propylene and at least 10 mol% of structural units derived from one or more monomers selected from ethylene and α-olefins having 4 to 20 carbon atoms. More preferably, it contains at least 91 mol% of structural units derived from propylene and at least 9 mol% of structural units derived from one or more monomers selected from ethylene and α-olefins having 4 to 20 carbon atoms (wherein the total of the two structural units is set to 100 mol%).
[0085] Examples of α-olefins with 4 to 20 carbon atoms include 1-butene, 3-methyl-1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.
[0086] As a method for manufacturing syndiotactic propylene polymers, the manufacturing method described in International Publication No. 2011 / 078054 can be cited as an example.
[0087] When the propylene polymer (A) contains propylene polymer (a-1), the content of propylene polymer (a-1) relative to the total mass of the propylene polymer (A) is preferably 50-80% by mass, more preferably 55-85% by mass, and even more preferably 60-80% by mass. When the content of polymer (a-1) is within the above range, the whitening resistance is excellent.
[0088] The propylene polymer (a-1) may contain only one type or two or more types. When it contains two or more types of propylene polymer (a-1), the content of the propylene polymer (a-1) is the total content of propylene polymer (a-1) contained in the propylene polymer (A).
[0089] The melt flow rate (MFR) of the aforementioned propylene polymer (A), measured according to ASTM D1238 at 230°C and a load of 2.16 kg, is preferably in the range of 0.01 to 1000 g / 10 min, more preferably in the range of 0.05 to 100 g / 10 min.
[0090] The propylene polymer (A) may contain at least one monomer derived from biomass. The same type of monomers constituting the propylene polymer (A) may be solely derived from biomass, solely derived from fossil fuels, or may include both monomers derived from biomass and monomers derived from fossil fuels.
[0091] Biomass-derived monomers refer to monomers formed from all renewable natural raw materials and their residues, including fungi, yeasts, algae, and bacteria, derived from plants or animals. As carbon, they contain 1 × 10⁻⁶ units. ﹣12 left and right proportions 14 The carbon isotope concentration (pMC) of the biomass, measured according to ASTM D6866, is approximately 100 (pMC). There are no particular restrictions on the synthesis method of the biomass-derived monomers (e.g., propylene, α-olefins with 2 to 20 carbon atoms (excluding propylene), etc.), and existing known methods can be used. From the viewpoint of reducing environmental impact, it is preferable that the propylene-based polymer (A) contains a biomass-derived monomer.
[0092] It should be noted that if the polymerization catalyst, polymerization temperature, and other polymer manufacturing conditions are the same, then even if the raw material olefin is a propylene-based polymer (A) containing olefins derived from biomass, except for 1×10 ﹣12 The ratio of left and right contains 14 Apart from the C isotope, its molecular structure is the same as that of propylene polymers (A) composed of monomers derived from fossil fuels, and its properties remain unchanged.
[0093] The propylene polymer (A) may contain at least one monomer derived from chemical recycling. The same type of monomers constituting the propylene polymer (A) may be solely derived from chemical recycling, or may include monomers derived from chemical recycling, monomers derived from fossil fuels, and / or monomers derived from biomass.
[0094] There are no particular restrictions on the synthesis method of monomers derived from chemical recycling (e.g., propylene, α-olefins with 2 to 20 carbon atoms (but excluding propylene)). For example, existing known methods can be used. From the viewpoint of reducing environmental impact (mainly reducing waste), it is preferable that the propylene polymer (A) contains monomers derived from chemical recycling. Monomers derived from chemical recycling are monomers obtained by depolymerizing and thermally decomposing polymers such as waste plastics back to monomer units such as propylene, as well as monomers manufactured from such monomers. Therefore, even if the raw material monomer is a propylene polymer containing monomers derived from chemical recycling, as long as the polymer manufacturing conditions such as the polymerization catalyst, polymerization process, and polymerization temperature are the same, the molecular structure is the same as that of the propylene polymer (A) composed of monomers derived from fossil fuels, and the properties remain unchanged.
[0095] <Modified Polyolefin (B)>
[0096] The modified polyolefin (B) contains structural units derived from at least one of unsaturated carboxylic acids and their derivatives. The modified polyolefin (B) is obtained by modifying an unmodified polyolefin (b) with at least one of unsaturated carboxylic acids and their derivatives.
[0097] Modified polyolefins (B) can be used alone or in combination of two or more.
[0098] As the unmodified polyolefin (b) mentioned above, polypropylene (b1) is a preferred example.
[0099] Polypropylene (b1) can be exemplified by homopolymers of propylene and copolymers of propylene-α-olefins.
[0100] The α-olefin in the above-mentioned propylene-α-olefin copolymer is not particularly limited, but is preferably ethylene and an α-olefin having 4 to 20 carbon atoms, more preferably ethylene and an α-olefin having 4 to 10 carbon atoms, and even more preferably ethylene and an α-olefin having 4 to 8 carbon atoms. The α-olefin can be a single type or two or more types.
[0101] The proportion of propylene-derived structural units in the propylene-α-olefin copolymer is at least 50 mol% and less than 100 mol% relative to all structural units of the copolymer.
[0102] Among these, from the viewpoint of excellent resistance to whitening, polypropylene (b1) is preferably a homopolymer of propylene.
[0103] The intrinsic viscosity [η] of polypropylene (b1) is preferably 0.1 to 10 dl / g. When the intrinsic viscosity [η] is within the above range, an adhesive film with excellent formability and mechanical strength can be obtained.
[0104] Polypropylene (b1) is preferably a crystalline polymer. When polypropylene (b1) is a copolymer, it can be a random copolymer, a block copolymer, or it can contain several different isotactic polypropylenes.
[0105] There are no particular limitations on the manufacturing method of polypropylene (b1). For example, manufacturing methods using known catalysts such as Ziegler-Natta catalysts and metallocene catalysts can be cited. Polypropylene (b1) can be obtained through synthesis or as a commercially available product.
[0106] Examples of unsaturated carboxylic acids and / or their derivatives used for modifying unmodified polyolefins (b) include: unsaturated compounds having one or more carboxyl groups per molecule; esters formed by compounds having carboxyl groups and alkyl alcohols; and unsaturated compounds having one or more structures represented by R-CO-O-CO-R' (where R and R' are each an independent hydrocarbon group) per molecule.
[0107] Unsaturated groups, which are present in unsaturated compounds, can be exemplified by vinyl groups, vinylidenes, and unsaturated cyclic hydrocarbon groups.
[0108] Among these, unsaturated carboxylic acids and their derivatives are preferred, especially unsaturated dicarboxylic acids and their anhydrides, particularly maleic acid, nadic acid and their anhydrides.
[0109] Unsaturated carboxylic acids and their derivatives can be used alone or in combination of two or more.
[0110] The content of structural units derived from unsaturated carboxylic acids and / or their derivatives in the modified polyolefin (B) described above (i.e., the amount of graft modification), converted to the content of structural units derived from maleic anhydride (i.e., assuming that the unsaturated carboxylic acid and / or its derivatives are maleic anhydride), is preferably 0.01 to 5% by mass, more preferably 0.05 to 3.5% by mass. When the content of structural units derived from unsaturated carboxylic acids and / or their derivatives is within the above range, the resulting adhesive film exhibits balanced and excellent formability and adhesion.
[0111] The content of propylene-derived structural units in the modified polyolefin (B), excluding those derived from the unsaturated carboxylic acid and / or its derivatives, is preferably 50 to 100 mol%, more preferably 80 to 100 mol%.
[0112] When the content ratio of the above-mentioned propylene-derived structural units is within the above range, an adhesive film with excellent heat resistance can be obtained.
[0113] There are no particular limitations on the method for modifying the unmodified polyolefin (b) with unsaturated carboxylic acids and / or their derivatives, and existing known graft polymerization methods such as solution polymerization and melt mixing can be used. Examples of such modification methods include melting the unmodified polyolefin (b) and then adding unsaturated carboxylic acids and / or their derivatives to carry out a grafting reaction; or dissolving the unmodified polyolefin (b) in a solvent to form a solution and then adding unsaturated carboxylic acids and / or their derivatives to carry out a grafting reaction.
[0114] The modified polyolefin (B) may contain at least one monomer derived from biomass. The same type of monomer constituting the modified polyolefin (B) may be solely derived from biomass, solely derived from fossil fuels, or may include both monomers derived from biomass and monomers derived from fossil fuels. It should be noted that the aforementioned monomers derived from biomass and monomers derived from fossil fuels are synonymous with the monomers derived from biomass and monomers derived from fossil fuels in the aforementioned propylene polymer (A).
[0115] In addition, the modified polyolefin (B) may contain at least one monomer derived from chemical recycling. The same type of monomers constituting the modified polyolefin (B) may be solely derived from chemical recycling, or may include monomers derived from chemical recycling, monomers derived from fossil fuels, and / or monomers derived from biomass.
[0116] It should be noted that the monomers derived from chemical recycling mentioned above are synonymous with the monomers derived from chemical recycling in the aforementioned propylene polymer (A).
[0117] <Vinyl Polymers (C)>
[0118] The above-mentioned ethylene polymer (C) satisfies the following (C1) to (C3).
[0119] [Condition (C1)]
[0120] The above-mentioned ethylene-based polymer (C) contains an ethylene-α-olefin copolymer (C-1).
[0121] [Ethylene-α-olefin copolymer (c-1)]
[0122] Examples of α-olefins in ethylene-α-olefin copolymers (c-1) include α-olefins with 3 to 20 carbon atoms. Examples of α-olefins with 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. Among these, propylene, 1-butene, 1-hexene, or 1-pentene are preferred as α-olefins with 3 to 20 carbon atoms.
[0123] The aforementioned α-olefins with 3 to 20 carbon atoms can be a single type or two or more types.
[0124] In the ethylene-α-olefin copolymer (c-1), the proportion of structural units derived from ethylene is preferably 30 to 99 mol%, more preferably 50 to 99 mol%.
[0125] In the ethylene-α-olefin copolymer (c-1), the content of structural units derived from α-olefins is preferably 1 to 70 mol%, more preferably 1 to 50 mol%. The total content of structural units derived from ethylene and structural units derived from α-olefins is set to 100 mol.
[0126] Furthermore, the melt flow rate (MFR) of the ethylene-α-olefin copolymer (c-1), measured according to ASTM D1238 at 230°C and a load of 2.16 kg, is preferably less than 10.0 g / 10 min, more preferably 0.5 to 9.0 g / 10 min, and even more preferably 0.5 to 8.5 g / 10 min.
[0127] [Condition (C2)]
[0128] The melt flow rate (MFR) of the above-mentioned ethylene polymer (C) measured according to ASTM D1238 at 230°C and a load of 2.16 kg is 0.1 to 10 g / 10 min, preferably 0.3 to 8 g / 10 min, and more preferably 0.5 to 6 g / 10 min.
[0129] When the MFR is within the above range, the resulting adhesive film has a balanced and excellent flexibility and mechanical strength, and also excellent adhesion.
[0130] On the other hand, when the MFR is below 10 g / 10 min, thinning during heat sealing is suppressed, ensuring that the resulting adhesive film has sufficient thickness. Therefore, when this adhesive film is used as an adhesive layer, it is easy to improve the adhesive strength. In addition, when the MFR is above 0.1 g / 10 min, the wettability with the substrate is excellent, thus making it easy to improve the adhesive strength.
[0131] From the viewpoint of flexibility, the density of the aforementioned vinyl polymer (C) is preferably between 855 and 970 kg / m³. 3 More preferably, it is within the range of 860–940 kg / m³. 3 Within the range of 865–930 kg / m³, it is further preferred. 3 Within the range.
[0132] [Condition (C3)]
[0133] The content of ethylene-α-olefin copolymer (c-1) relative to the total mass of the ethylene polymer (C) is 40 to 100% by mass, preferably 40 to 80% by mass from the viewpoint of excellent whitening resistance, more preferably 40 to 70% by mass, and even more preferably 40 to 60% by mass. When the ethylene polymer (C) contains two or more types of ethylene-α-olefin copolymer (c-1), the content of the ethylene-α-olefin copolymer (c-1) is the total content of the copolymers (c-1) contained in the ethylene polymer (C).
[0134] Ethylene polymers (C) may contain ethylene homopolymers (C-2).
[0135] The content of ethylene homopolymer (c-2) relative to the total mass of ethylene polymer (C) is preferably 0 to 60% by mass, more preferably 20 to 60% by mass, even more preferably 30 to 60% by mass, and particularly preferably 40 to 60% by mass.
[0136] The ethylene polymer (C) can be a single type or two or more types used together.
[0137] When the ethylene polymer (C) contains two or more ethylene homopolymers (c-2), the content of the ethylene homopolymer (c-2) is the total content of the ethylene homopolymer (c-2) contained in the ethylene polymer (C).
[0138] There are no particular limitations on the manufacturing methods of the above copolymer (c-1) and ethylene homopolymer (c-2), and they can be manufactured by high pressure method or known methods using known catalysts such as Ziegler-Natta catalysts or metallocene catalysts.
[0139] The copolymer (c-1) and homopolymer (c-2) mentioned above may also be commercially available products.
[0140] As long as the above (C1) to (C3) are satisfied, the ethylene polymer (C) can be grafted with a small amount of maleic anhydride, etc., or it can be grafted with a small amount of maleic anhydride, etc., and then the grafted monomer can be further modified with diamine, carbodiimide, etc.
[0141] From the viewpoint that when a composition comprising a propylene polymer (A), a modified polyolefin (B), and a vinyl polymer (C) is formed, the gel component in the composition is reduced and the appearance of the adhesive film after film formation is superior, the vinyl polymer (C) is preferably not grafted modified.
[0142] The ethylene polymer (C) may contain at least one type of monomer derived from biomass. The same type of monomer constituting the ethylene polymer (C) may be solely derived from biomass, solely derived from fossil fuels, or may include both. It should be noted that the aforementioned monomers derived from biomass and monomers derived from fossil fuels are synonymous with the aforementioned monomers derived from biomass and monomers derived from fossil fuels in the propylene polymer (A).
[0143] When the ethylene polymer (C) contains monomers derived from biomass (such as ethylene and α-olefins with 3 to 20 carbon atoms), there are no particular restrictions on the synthesis method of the monomers derived from biomass, and existing known methods can be used.
[0144] In addition, the ethylene polymer (C) may contain at least one monomer derived from chemical recycling. The same type of monomers constituting the ethylene polymer (C) may be solely derived from chemical recycling, or may include monomers derived from chemical recycling, monomers derived from fossil fuels, and / or monomers derived from biomass.
[0145] It should be noted that the monomers derived from chemical recycling mentioned above are synonymous with the monomers derived from chemical recycling in the propylene polymer (A) mentioned above. When the ethylene polymer (C) contains monomers derived from chemical recycling (e.g., ethylene and α-olefins with 3 to 20 carbon atoms), there are no particular restrictions on the synthesis method of the monomers derived from chemical recycling, and existing known methods can be used.
[0146] Without impairing the effects of the present invention, the adhesive film may also contain components other than propylene polymer (A), modified polyolefin (B), and ethylene polymer (C) (hereinafter also referred to as "other components"). Examples of other components include: antioxidants, ultraviolet absorbers, neutralizers, nucleating agents, light stabilizers, antistatic agents, antiblocking agents, slip agents, odor absorbers, antibacterial agents, hygroscopic agents, pigments, inorganic or organic fillers, and other polymers other than propylene polymer (A), modified polyolefin (B), and ethylene polymer (C).
[0147] The content of the additive is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to a total of 100 parts by mass of propylene polymer (A), modified polyolefin (B) and ethylene polymer (C).
[0148] In the adhesive film, the content of propylene polymer (A) is 50-89.9 parts by mass, the content of modified polyolefin (B) is 0.1-20 parts by mass, and the content of ethylene polymer (C) is 10-30 parts by mass; preferably, the content of propylene polymer (A) is 50-87.5 parts by mass, the content of modified polyolefin (B) is 0.5-20 parts by mass, and the content of ethylene polymer (C) is 12-30 parts by mass; more preferably, the content of propylene polymer (A) is 50-84 parts by mass, the content of modified polyolefin (B) is 1-20 parts by mass, and the content of ethylene polymer (C) is 15-30 parts by mass. The total content of propylene polymer (A), modified polyolefin (B), and ethylene polymer (C) is set at 100 parts by mass.
[0149] When the contents of the propylene polymer (A), modified polyolefin (B), and ethylene polymer (C) in the adhesive film are within the above range, the reduction in adhesion is suppressed.
[0150] When the content of propylene polymer (A) is 50 parts by mass or more, it is easy to obtain initial adhesive strength.
[0151] One preferred embodiment is that the content of the vinyl polymer (C) is 12.5 to 30 parts by weight or 13 to 30 parts by weight. When the content of the vinyl polymer (C) is within the above range, the adhesive film exhibits excellent stability during film formation.
[0152] There are no particular limitations on the manufacturing method of the adhesive film, and known manufacturing methods can be used. For example, a method for manufacturing the adhesive film may be to melt-blend a resin composition comprising the above-mentioned propylene polymer (A), modified polyolefin (B) and ethylene polymer (C), and then melt-extrude the resin composition, for example.
[0153] Furthermore, there are no particular limitations on the forming method for adhesive films; for example, casting, blow molding, and extrusion lamination can be used. Among these, casting is preferred from the viewpoint of achieving excellent film-forming precision.
[0154] The film traction speed in the casting process is not particularly limited and can be appropriately set within a range that does not impair the effects of the present invention. From the viewpoint of obtaining a suitable morphology in the adhesive film, the film traction speed in the casting process is preferably 5 to 50 m / min, more preferably 10 to 40 m / min.
[0155] When the film traction speed in the casting process is within the above range, it is easy to adjust the area ratio of the island phase to 17-28%, and the resulting adhesive film has better resistance to whitening during deformation processing.
[0156] There are no particular limitations on the extruder used to melt the above-mentioned resin composition during the molding of the adhesive film; any known extruder can be used. Examples of extruders include single-screw extruders and twin-screw extruders.
[0157] In an extruder, the ratio (L / D) of the barrel length (L) to the internal screw diameter (D) is not particularly limited, but from the viewpoint of suppressing resin deterioration, it is preferably in the range of 10 to 50, more preferably in the range of 15 to 40, and even more preferably in the range of 20 to 35.
[0158] The above (L / D) is one of the indicators representing the performance of an extruder.
[0159] There are no particular limitations on the barrel temperature, as long as it is the melting temperature of the above-mentioned resin composition. From the viewpoint of suppressing resin deterioration, the barrel temperature is preferably 180 to 270°C, and more preferably 200 to 240°C.
[0160] There are no particular limitations on the die head temperature, as long as it is the melting temperature of the aforementioned resin composition. From the viewpoint of suppressing resin deterioration, the die head temperature is preferably 180–270°C, and more preferably 200–240°C.
[0161] Single-layer or multi-layer membranes
[0162] The single-layer or multi-layer film of the present invention has the above-mentioned adhesive properties.
[0163] Multilayer films can have only one layer of the above-mentioned adhesive film, or they can have multiple layers.
[0164] The multilayer film preferably has at least one adhesive film and at least one layer selected from the metal layer, polyolefin layer and polar resin layer, and the adhesive film is in contact with the at least one layer selected from the metal layer, polyolefin layer and polar resin layer.
[0165] Examples of metal layers include aluminum layers (e.g., aluminum foil), copper layers, and stainless steel layers.
[0166] As a polyolefin layer, there are no particular restrictions as long as it is a layer other than an adhesive film. Examples include polypropylene layers, poly(4-methylpentene) layers, and polyethylene layers.
[0167] Examples of polar resin layers include polyamide layers, EVOH (ethylene alcohol copolymer) layers, PET (polyethylene terephthalate) layers, and PBT (polybutylene terephthalate) layers.
[0168] There are no particular limitations on the forming method of multilayer films; for example, casting, blow molding, and extrusion lamination can be used. Among these, extrusion lamination is preferred from the viewpoint of low production cost.
[0169] From the perspective of superior resistance to whitening, adhesive films and single-layer or multi-layer films are preferred for use as battery packaging films such as lithium battery packaging films or electrode sealing materials for lithium-ion batteries.
[0170] Example
[0171] The present invention will now be described in more detail based on embodiments, etc., but the present invention is not limited to these embodiments in any way.
[0172] [Methods for determining physical properties]
[0173] Melt Flow Rate (MFR)
[0174] (1) The MFR of propylene polymers and components constituting island and marine phases was determined according to ASTM D1238 at a temperature of 230°C and a load of 2.16 kg.
[0175] (2) The MFR of ethylene polymers was determined according to ASTM D1238 at a temperature of 230°C and a load of 2.16 kg.
[0176] (3) When the ethylene polymer contains two or more copolymers (c-1) and ethylene homopolymers (c-2), “MFR of ethylene polymer” refers to the value calculated by the logarithmic addition rule of the MFR of each ethylene polymer.
[0177] (4) MFR of components constituting island and marine facies
[0178] The mean free float (MFR) of the components constituting the island and marine phases was determined separately for each component according to ASTM D1238 at 230°C and a load of 2.16 kg. It should be noted that when there are two or more components constituting either the island or marine phases, the MFR of each component was calculated using the logarithmic addition method.
[0179] The MFR of the island phase = (MFR of island phase component 1)^(Containment ratio of component 1 in the island phase) × (MFR of island phase component 2)^(Containment ratio of component 2 in the island phase) × ...
[0180] <Density>
[0181] The density was determined according to JIS K7112 (density gradient tube method).
[0182] <Proportion of structural units>
[0183] pass 13 C-NMR was used to quantify the content of structural units derived from ethylene or propylene in polymers using the following apparatus and conditions.
[0184] Nuclear magnetic resonance (NMR) equipment (JECX400P, manufactured by NJE Ltd) was used under the following conditions: a mixed solvent of deuterated o-dichlorobenzene / deuterated benzene (80 / 20 volume %) was used as the solvent; the sample concentration was 60 mg / 0.6 mL; the measurement temperature was 120 °C; and the observed nuclei were... 13 C (100MHz), the sequence was decoupled by single-pulse protons with a pulse width of 4.62μs (45° pulse), a repetition time of 5.5 seconds, and a cumulative count of 8000 times, with 29.73ppm as the reference value for chemical shift.
[0185] <<Propylene Polymers (A)>>
[0186] • Propylene polymers (a-1):
[0187] Marine phase composition 1: atactic polypropylene, MFR (230℃, load 2.16kg) = 4.8g / 10min, density = 895kg / m³ 3 Melting point = 130℃, ethylene content = 2.8 mol%, butene content = 5.1 mol%.
[0188] Marine phase component 2: homopolymer polypropylene, MFR (230℃, load 2.16kg) = 0.5g / 10min, density = 903kg / m³ 3 Melting point = 165℃
[0189] • Propylene polymers (a-2):
[0190] Marine phase component 3: PBR (propylene-butene copolymer), MFR (230℃, load 2.16kg) = 7.0g / 10min, density = 884kg / m³ 3 Melting point = 80℃, butene content = 26 mol%.
[0191] <<Modified Polyolefin (B)>>
[0192] Marine phase component 4: Maleic anhydride modified homopolymer polypropylene (MFR (230℃, load 2.16kg) = 1000g / 10min, density = 900kg / m³) 3 )
[0193] <<Vinyl Polymers (C)>>
[0194] • Ethylene-based polymers (c-1): EPR (ethylene-propylene copolymer, propylene content = 20 mol%)
[0195] The compositions of island phase components 1 to 3 described below are the same as those of the EPR described above.
[0196] Island phase composition 1: MFR (230℃, load 2.16kg) = 0.8g / 10min, density = 869kg / m³ 3
[0197] Island phase component 2: MFR (230℃, load 2.16kg) = 5.4g / 10min, density = 869kg / m³ 3
[0198] Island phase component 3: MFR (230℃, load 2.16kg) = 8.1g / 10min, density = 869kg / m³ 3
[0199] • Ethylene-based polymers (c-2): PE (polyethylene)
[0200] It should be noted that the components of island phases 4 and 5 are both composed of PE.
[0201] Island phase component 4: MFR (230℃, load 2.16kg) = 2.3g / 10min, density = 919kg / m³ 3
[0202] Island phase component 5: MFR (230℃, load 2.16kg) = 0.6g / 10min, density = 921kg / m³ 3
[0203] <Preparation of Adhesive Resin Compositions>
[0204] According to the composition ratios of Examples 1 and 2 and Comparative Examples 1 to 3 as described in Table 1, propylene polymer (A), modified polyolefin (B) and ethylene polymer (C) were melt-blended using a single-screw extruder at a temperature of 230°C to prepare adhesive resin compositions.
[0205] <Example 1>
[0206] The adhesive film of Example 1 was prepared as described below.
[0207] The adhesive resin composition prepared as described above was extruded at 240°C using a screw with a diameter of 50 mm and a barrel length (L) to internal screw diameter (D) ratio (L / D) of 28, to produce a 50 μm thick polypropylene monolayer film at a traction speed of 10 m / min. The die temperature was 240°C.
[0208] [Evaluation of whitening resistance after deep drawing]
[0209] Commercially available polypropylene (manufactured by Priman Polymers Co., Ltd., product name: F327, MFR (230℃, load 2.16kg): 7.0g / 10min) was extruded at 240℃ using a screw with a diameter of 50mm and a barrel length (L) to internal screw diameter (D) ratio (L / D) of 28, to produce a single-layer film with a thickness of 50μm at a traction speed of 10m / min. The die temperature was 240℃.
[0210] The polypropylene monolayer film prepared as described above is overlapped with the adhesive film prepared as described above, and then an aluminum foil (70 μm thick) is overlapped on the adhesive film. The film is then extruded (extrusion lamination) using a benchtop hot lamination apparatus (Tester Industrial Co., Ltd., model: SA-1010-S) at 190°C, 0.2 MPa, and 0.5 m / min to produce a multilayer film.
[0211] The obtained multilayer film was deep-drawn using a die with an engagement depth of 5 mm to obtain a molded body. The degree of whitening on the wall surface of the molded body was visually observed and evaluated according to the following criteria.
[0212] B: It has been confirmed that all or part of the deep-drawn portion of the molded body has turned white.
[0213] A: No whitening was observed in the deep-drawing portion of the molded part.
[0214] [Area ratio of island facies to marine facies]
[0215] The adhesive film prepared as described above was cut into test pieces using a slicer, forming a cross-section perpendicular to the film surface and including the MD direction. The test pieces were stained and observed at 1000x magnification using a transmission electron microscope (TEM) (JEOL Ltd., JSM-IT700HR) in reflected electron mode.
[0216] [Image Processing Conditions]
[0217] The area of the obtained TEM image of the test piece was 250 μm, obtained using the image analysis software ImageJ. 2Image processing was performed. PNG format digital files of the TEM images were obtained. After thresholding and binarization of the interface between marine and island facies, the area ratio of the island facies was calculated using particle resolution mode. The results are shown in Table 1.
[0218] The ratio of the MFR of marine components to the MFR of island components (MFR) A / MFR B )]
[0219] The MFR of the components constituting the island phase (MFR of the island phase) was calculated using the MFR of the ethylene polymer (B), and the MFR of the components constituting the marine phase (MFR of the marine phase) was calculated using the MFR of the propylene polymer (A) and the modified polyolefin (B). The MFR of each component was calculated using the logarithmic addition rule.
[0220] The MFR of the island phase in Example 1 was obtained as follows.
[0221] The MFR of the island phase = (MFR of island phase component 1: 0.8)^((Percentage of island phase component 1 in the island phase: 5.5) / (5.5+7.0)) × (MFR of island phase component 4: 2.3)^((Percentage of island phase component 4 in the island phase: 7.0) / (5.5+7.0)) ≈ 6.0
[0222] The MFR of the marine facies in Example 1 was obtained as follows.
[0223] The MFR of a marine facies is calculated as follows: (MFR of marine component 1: 4.8)^((Percentage of marine component 1 in the marine facies: 48) / (48 + 7.5 + 27 + 5.0)) × (MFR of marine component 2: 0.5)^((Percentage of marine component 2 in the marine facies: 7.5) / (48 + 7.5 + 27 + 5.0)) × (MFR of marine component 3: 7.0)^((Percentage of marine component 3 in the marine facies: 27) / (48 + 7.5 + 27 + 5.0)) × (MFR of marine component 4: 7.0)^((Percentage of marine component 4 in the marine facies: 5.0) / (48 + 7.5 + 27 + 5.0)) ≈ 1.4
[0224] Marine MFR / Island MFR (MFR) A / MFR B ≈4.2
[0225] It should be noted that "the percentage of marine component 1 in marine facies" refers to the percentage (mass %) of marine component 1 relative to all components of marine facies, and "the percentage of island component 1 in island facies" refers to the percentage (mass %) of island component 1 relative to all components of island facies.
[0226] <Example 2 and Comparative Examples 1-3>
[0227] Except for using the adhesive resin composition prepared according to the composition described in Table 1, adhesive films and multilayer films were prepared in the same manner as in Example 1. The MFR ratio of the marine phase component to the island phase component was determined in the same manner as in Example 1. A / MFR B In addition, the whitening resistance was evaluated using the same procedure as in Example 1. The results are shown in Table 1.
[0228] [Table 1]
[0229]
[0230] Comparing the adhesive films of Example 1 and Comparative Example 1, it can be seen that by adjusting the area ratio of the island phase and the marine phase in the adhesive film, the morphology changes. As a result, compared with the adhesive film of Comparative Example 1, the whitening of the adhesive film during deformation is suppressed, that is, the whitening resistance during deformation processing is excellent.
[0231] As shown in Table 1, the multilayer films of Examples 1 and 2 exhibit superior resistance to whitening during deformation processing compared to the multilayer films of Comparative Examples 1 to 3.
Claims
1. An adhesive film, characterized in that, contain: 50 to 89.9 parts by weight of propylene polymer (A) that meets the following (A1); 0.1 to 20 parts by weight of modified polyolefin (B) containing structural units derived from at least one of unsaturated carboxylic acids and their derivatives; and 10-30 parts by weight of ethylene-based polymer (C) satisfying (C1) to (C3) below, wherein the total of (A), (B) and (C) is set at 100 parts by weight. The area proportion of island phases observed in cross-sections perpendicular to the membrane surface and including the MD direction is 17–28%. (A1) The content of propylene polymer (a-2) with a melting point (Tm) less than 120°C as observed in differential scanning calorimetry in the propylene polymer (A) is 20-100% by mass relative to the total mass of the propylene polymer (A). (C1) contains an ethylene-α-olefin copolymer (c-1). (C2) The melt flow rate, measured according to ASTM D1238 at 230°C and a load of 2.16 kg, is 0.1–10 g / 10 min. (C3) The content of the ethylene-α-olefin copolymer (c-1) relative to the total mass of the ethylene polymer (C) is 40 to 100 by mass.
2. The adhesive film according to claim 1, characterized in that: The composition of the marine phase observed in a cross-section perpendicular to the film surface and including the MD direction, and the melt flow rate A measured according to ASTM D1238 at 230°C and a load of 2.16 kg, are compared with... The composition of island phases observed in a cross-section perpendicular to the film surface and including the MD direction is the ratio of the melt flow rate B, measured according to ASTM D1238 at 230°C and a load of 2.16 kg, to the melt flow rate B, i.e., the MFR. A / MFR B It is between 2 and 5.
3. A single-layer or multi-layer film, characterized in that: The single-layer or multi-layer film has the adhesive properties described in claim 1 or 2.
4. A multilayer film, characterized in that, have: At least one layer of the adhesive film as described in claim 1 or 2; and Selected from at least one layer comprising a metal layer, a polyolefin layer, and a polar resin layer. The adhesive membrane is in contact with at least one layer selected from the metal layer, the polyolefin layer, and the polar resin layer.
5. The adhesive film according to claim 1, characterized in that: This adhesive film is used for battery packaging.
6. The adhesive film according to claim 1, characterized in that: This adhesive film is an electrode sealing material for lithium-ion batteries.
Citation Information
Patent Citations
Resin composition and monolayer and multilayer films
WO2019176403A1
Adhesive resin composition and film
WO2023022168A1